KARAKTERISTIK HIDROLOGI PADA DUA DAS KECIL DI WILAYAH UPT PSDA DI SURABAYA : ANALISIS MENGGUNAKAN INDICATORS OF HYDROLOGIC ALTERATION (IHA) - Indarto Indarto; Isfi roni Rohman; Idah Andriyani (School of Postgraduate Studies, Diponegoro Univer, 2019)
This research proposes to evaluate whether there has been a change in hydrological regimes of the watershed. The research was conducted at the the administrative area of UPT PSDA Surabaya. Furthermore, Surabaya-Perning and Lamong-Simoanggrok watersheds were used as a sample for this study. The analysis was conducted using the Indicator of Hydrologic Alteration (IHA). The main input is the daily discharge data series from the two watersheds. The discharge data range from 1996 to 2015. Then, the time series data is divided into two periods, the pre-impact period (1996-2005) and the post-impact period (2006-2015). A total of 33 IHA parameters classified into 5 categories were used to evaluate the change. The results of the assessment are then used for RVA (Range of Variable approach) calculations. RVA calculations were used to discover changes occurring from the pre-impact period to the post-impact period. The data series from the two watersheds also analyzed using Environmental Flow Components (EFC) and Flow Duration Curves (FDC). The result of the research shows the difference in parameter value that indicating the hydrological change between the pre-impact period and the post-impact period. RVA analysis results show an increased flow in the Surabaya-Perning watershed from January to September and December. RVA analysis results also show an increased flow in the Lamong-Simoanggrok watershed from January to July and December. The results of the EFC analysis can provide information about flows that have the potential to cause floods and droughts. The Surabaya-Perning watershed has the potential to encounter a small flood with a value 254,7 m3/s which last for 9 days with a chance of occurring 0,5 times every 2 years.